Disease Spectral Identification and Analysis on the Bark of Gmelina (Gmelina arborea Roxb) - Ayag, Annie Onez; Padonat, Kyra Luminarias; Minguita, Kizza Eyn Sulima; Vergara, Joey Arles Ongue; Jusoy, Jade Capinpuyan; Casilac Jr, Cornelio Sacquiap (Jurnal Sylva Lestari, 2025)
Gmelina arborea is among the fast-growing Industrial tree plantation species currently being used as an alternative source of the decreasing supply of commercial timber from natural-growth forests. This study focuses on disease spectral identification and analysis of G. arborea bark using UV-Vis Spectrophotometry. Bark samples from both healthy and unhealthy bark with canker and death diseases were collected inside Caraga State University’s Main Campus. The methodology involved preparing bark extracts and measuring their absorbance over a wavelength range of 350 nm to 800 nm. The findings revealed distinct spectral signatures of healthy and unhealthy cankers, particularly with death disease, which exhibits a greater alteration in its spectral trend. The spectral trend of death-disease shows a drastic decrease in its absorption and the presence of troughs and peaks. On the other hand, the canker shows a decrease in its absorption. The severity of disease in the bark may potentially affect the behavior of the spectral trend; this is proven in the spectral trend of death-disease. The absorbance decreased, causing troughs at specific wavelengths as the presence of those diseases and their severity progressed. These findings show that spectral information from healthy and unhealthy bark can be used as an early detection method for tree diseases or stresses, thereby contributing to the conservation and sustainable use of G. arborea. Keywords: disease identification, healthy bark, Gmelina arborea, unhealthy bark, UV-Vis spectrometry